Ethnomedicinal study on the Tajpuriya community in Shivasatakshi Municipality, Jhapa district, eastern Nepal - Tajpuriya, Sapana; Shrestha, Ila; Sharma, Deepak Kumar; Silwal Gautam, Ratna (Ethnobotany Research and Applications, 2026)
Background: Traditional medicine plays a crucial role in the healthcare system of Nepal. Various ethnic groups rely on locally available plants, preserving the ethnomedicinal knowledge. The present study aimed to document the traditional medicinal plant knowledge of the Tajpuriya, an ethnic group of eastern Nepal, through an ethnomedicinal survey conducted in Jhapa District. Method: An ethnomedicinal study was conducted through interviews employing semi-structured, open-ended questionnaires with 52 informants, including two key informants. Spearman’s correlation analysis was applied to examine the relationship between informant’s age and ethnomedicinal knowledge, while the Wilcoxon rank-sum test was used to evaluate gender-based differences in ethnomedicinal knowledge. Quantitative indices, including the Informant Consensus Factor (ICF) was computed to evaluate the degree of shared knowledge among informants about traditional treatments, and the Relative Frequency of Citation (RFC) was determined to identify the common medicinal plants in the study area. Results: This study recorded 61 plant species from 39 families and 57 genera, treating 13 disease categories. The Wilcoxon test showed significant gender variations in plant knowledge (p = 0.005) and Spearman’s correlation revealed a strong positive relation between age of informants and species cited (r = 0.687, p < 0.001). Among the documented species, herbs (38 spp.) represented the dominant growth form, while leaves (23 spp.) were the most commonly utilized plant parts. Juice (31 spp.) was the predominant form of preparation, while oral intake (40 spp.) was the most frequently reported route of administration. The highest ICF was recorded for ear and neurological disorders, whereas digestive disorders involved the largest number of species used (21 spp.). Eclipta prostrata and Centella asiatica showed the highest values of RFC. Conclusions: This study documented the ethnomedicinal information from the Tajpuriya ethnic group in Shivasatakshi Municipality, Jhapa District, highlighting the need for preservation of biocultural heritage and providing a valuable foundation for future pharmacological studies and drug discovery. Keywords: Medicinal plants, Traditional knowledge, Age, Gender